Clinical Impact of Antifungal Susceptibility, Biofilm Formation and Mannoside Expression of Candida Yeasts on the Outcome of Invasive Candidiasis in ICU: An Ancillary Study on the Prospective AmarCAND2 Cohort - Gangneux, Jean-Pierre; Cornet, Muriel; Bailly, Sébastien; Fradin, Chantal; Féger, Céline; Timsit, Jean-François; Leroy, Olivier; Sendid, Boualem; Bougnoux, Marie-Elisabeth (Frontiers in Microbiology, 2018)
The link between Candida phenotypical characteristics and invasive candidiasis (IC) prognosis is still partially unknown. In this work, Candida strains isolated during the AmarCAND2 study were centrally analysed for species identification, antifungal susceptibility, biofilm formation, and expression of surface and glycoconjugate mannosides. Correlation between these phenotypical features and patient outcome was sought using a multivariable Cox survival model. Candida albicans was predominant (65.4%, n=285), with a mortality rate significantly lower than that in patients with non-albicans strains (HR 0.67 [0.46-1.00], p=.048). The rate of fluconazole-resistant strains was low (C. albicans and C. glabrata: 3.5% and 6.2%, respectively) as well as caspofungin-resistant ones (1% and 3.1%, respectively). Early biofilm formation was less frequent among C. albicans (45.4%) than among non-albicans (81.2%). While the strains of C. albicans showed variable levels of surface mannosides expression, strains isolated from candidemia exhibited a high expression of β-man, which was correlated with an increased mortality (p=0.02).In conclusion, C. albicans IC were associated with lower mortality, and with strains that exhibited less frequently early biofilm formation than non-albicans strains. A high expression of β-man was associated with increased IC mortality. Further studies are warranted to confirm this data and to evaluate other virulence factors in yeasts.